Parent’s perception on factors contributing to teen pregnancy: A case study in Kota Samarahan, Sarawak / Nur Annisa Azman & Nor Faten Nasoha Ismail - Azman, Nur Annisa; Ismail, Nor Faten Nasoha (2017)
This study consists with seven (7) sections. The first sections (Section 1.1) discuss and deliberate briefly on the background of study. On the other hand, the second section (Section 1.2) discuss deeply on the problem statement. Meanwhile on the third section (Section 1.3) provides all the research questions, whereas the fourth (Section 1.4) focuses on the research objectives. Apart from that, the fifth sections (Section 1.5) explain on scope of study followed by section sixth (Section 1.6) clarify on the significance of the study. Finally, on the section seventh (Section 1.7) elaborated on the definition of terms or concepts that has being used in this study.